Computation Of Neumann Localised Boundary Domain Integral Equations - N.A. Mohamed; N.F. Ibrahim; N.F. Mohamed; N.I. Norddin; N.H. Mohamed (ASM Science Journal, 2024)
ASM Science Journal Volume 18 Issue 2023 Page (1-8)